Effects of adrenergic stimulation and/or insulin on the myocardial glucose transporter, GLUT 4, glucose uptake and characteristics of the adrenergic receptor populations in normal and non-insulin dependent diabetes mellitus (NIDDM) rats - Van Dyk, Magdalena (Stellenbosch : Stellenbosch University, 2012)
One copy microfiche.